Cytochemical stainings in acute promyelocytic leukemia: chloroacetate esterase reaction as a prognostic index. - S. Chinprasertsuk (2018)
Cytochemical studies including peroxidase, sudan black B and esterases were used for staining peripheral blood and bone marrow smears from 42 patients with acute promyelocytic leukemia. The most sensitive methods were sudan black B (mean 98%, range 81-100%) and peroxidase (mean 92% range 70-100%). Naphthol AS-D chloroacetate esterase activity was less sensitive and was positive in only 49.4 per cent (range 2-100%). All of the population of leukemic cells contained less than 3 per cent of alpha-naphthyl acetate esterase staining. For stability tests of the storage specimens compared to fresh stains, there was no difference in naphthol AS-D chloroacetate esterase (mean 45% vs 49% P greater than 0.7) and sudan black B (mean 74% vs 98% P greater than 0.3), but the enzyme activity was significantly decreased in peroxidase staining (mean 42% vs 92% P greater than 0.05). When the patients were divided into 2 groups according to the degree of AS-D chloroacetate esterase activity, those with lower activity had a higher number of white blood cells, promyelocytes and shorter survival compared to those with higher activity. Therefore, naphthol AS-D chloroacetate esterase may be useful as a prognostic index.